Early Stage In Identifying Autism Spectrum Disorder (ASD) Through Screening And Diagnosis - Che Ku Mohd, Che Ku Nuraini; Shahbodin, Faaizah; Suparjoh, Suriawati; Che Amran, Aliza; Mohd Noor, Helmi Adly (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The objective of the paper was to evaluate developed screening tools on autism students’ as early detection detect early signs especially on visual for ASD children. The outcomes of early intervention in ASD can be improved but it depends types of the treatment. Method of collecting data was using tool, observation and interview. In design, flowchart and storyboard are produced. While in development stage, learning media and materials are presented with visualization in the form of sound, text, videos and pictures. The results of this study are a positive score and feedback from children with ASD. They are easy to focus in using this tool instead of conventional screening tool. The students really attract to something that related to technology. However, the suggestion of a screening for ASD when concerning from their parents or family. The quality of the instruments and screening procedure are the challenges faced during the process. The advantages of early screening and detection among ASD is very to avoid parents unnecessary worry among parents.